STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DALAM MEMBENTUK KARAKTER RELIGIUS VERTIKAL DAN HORIZONTAL SISWA: STUDI KASUS KOMPARATIF DI SD NEGERI 095/VIII KARANG DADI DAN SD NEGERI 124/VIII SIDO REJO - Padriyah KrisnaWardani; Eliva Sukma Cipta; Fitriyani Kosasih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze and compare the strategies of Islamic Religious Education (IRE) learning in fostering students' vertical and horizontal religious character at SD Negeri 095/VIII Karang Dadi and SD Negeri 124/VIII Sido Rejo. The research was motivated by the importance of strengthening religious character as an integral part of students' holistic development in elementary schools. A qualitative approach with a comparative case study design was employed. Data were collected through observation, documentation, and in-depth analysis of learning activities conducted in both schools. The data were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings indicate that both schools implemented Islamic Religious Education learning strategies through religious habituation, teacher role modeling, active learning, and the reinforcement of a religious school culture. However, differences were found in the implementation of these strategies. SD Negeri 095/VIII Karang Dadi emphasized continuous religious habituation to strengthen students' vertical religious character, while SD Negeri 124/VIII Sido Rejo focused more on participatory and collaborative learning activities that effectively promoted students' horizontal religious character. Overall, the integration of instructional strategies, religious practices, and supportive school culture contributed significantly to developing students' religious attitudes, moral behavior, social responsibility, discipline, and interpersonal relationships. The study concludes that systematic and contextual Islamic Religious Education learning strategies effectively foster both vertical and horizontal religious character among elementary school students.